Removal of copper(ii) ions from aqueous solutions using alginic acid: kinetics and isotherm studies - Tran , Vinh Thien (Journal of Technical Education Science, 2012)
The adsorption of Cu(II) ions from aqueous solution onto alginic acid has been investigated based on the establishment of a relationship among pH, conductivity and the concentration of metal ion. It was shown that the adsorption of this metal ion onto alginic acid followed the pseudo-second-order reaction and was conducted by ion exchange mechanism. Adsorption isotherm was analyzed by using Langmuir, Freundlich, Tempkin and Redlich-Peterson isotherm models. The Langmuir model was found to be the best fitting with the data of copper(II) ion sorption onto alginic acid. From the study on the effect of temperature, thermodynamic parameters were evaluated